Intravascular volumes evaluated by a carbon monoxide rebreathing method in patients undergoing chronic hemodialysis. Issue 2 (12th February 2020) - Bomholt, Tobias; Larsson, Sara; Rix, Marianne; Rytter, Sarah; Feldt‐Rasmussen, Bo; Hornum, Mads; Lundby, Carsten
Abstract: Introduction: Treatment of fluid overload and anemia remains a challenge in patients undergoing hemodialysis. Hypervolemia can be evaluated using a carbon monoxide (CO) rebreathing method by which blood volume (BV), plasma volume (PV), and red blood cell volumes (RBCV) can be determined. We hypothesized that recurrent hypervolemia would cause hemoglobin (Hb) levels to be in the anemic range without a concurrent reduction in RBCV in patients undergoing hemodialysis. Methods: BV, PV, and RBCV were determined by a CO rebreathing test in 19 patients with type 2 diabetes undergoing chronic hemodialysis. The tests were performed 20 minutes before initiating dialysis, and the measured intravascular volumes were compared with predicted normal intravascular volumes according to Nadler's equation. Before initiating dialysis, Hb and blood pressure were measured, and edema severity was graded. Findings: Measured BV was higher in 17 out of the 19 patients with a median of 71.1 (62.4–76.9) mL/kg and higher than the predicted BV of 58.3 (53.5–59.9) mL/kg ( P < 0.001). The measured PV was found to be higher in all patients. RBCV was measured as 25.2 (23.4–28.2) mL/kg with a predicted volume of 25.9 (22.4–26.7) mL/kg ( P = 0.56). Eighteen patients were anemic as determined by Hb concentrations (defined as Hb < 13 g/dL for men and <12 g/dL for women), and nine were anemic according to RBCV. Discussion: The CO rebreathing test is a new approach to measuring intravascular volumes in hemodialysis patients. Compared with predicted intravascular volumes, the predialysis BV was expanded in the majority with elevated PV as the main cause. No overall difference in RBCV was found between the measured and predicted volumes. According to predialysis Hb levels, all but one patient was anemic, but according to the measured RBCV, only nine were in the anemic range, indicating dilution of Hb.